Composite lithium iron phosphate and preparation method thereof, positive pole piece and secondary battery
By designing a composite lithium iron phosphate structure, combining lithium iron phosphate in the core-deficient phase with a carbon shell material as a lithium replenisher, the problems of low discharge capacity and low initial coulombic efficiency of lithium iron phosphate materials are solved, achieving efficient lithium-ion transport and improved battery performance.
Patent Information
- Application Number
- CN202511463776.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2045-10-14
AI Technical Summary
The actual discharge capacity of lithium iron phosphate materials is low, and the initial coulombic efficiency of secondary batteries using lithium iron phosphate materials is low.
The design employs a composite lithium iron phosphate structure, with the core consisting of lithium iron phosphate particles in the lithium-deficient phase and the shell consisting of carbon materials and lithium replenishing agent particles. The lithium ions in the shell are used to replenish the lithium vacancies in the core and form an SEI film, while the carbon materials protect the core and the shell.
It improves the discharge specific capacity, cycle performance and first coulombic efficiency of composite lithium iron phosphate, and enhances the charge-discharge stability and service life of secondary batteries.
Smart Images

Figure CN120933351A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, specifically to a composite lithium iron phosphate and its preparation method, a positive electrode sheet, and a secondary battery. Background Technology
[0002] Lithium iron phosphate (LiFePO4, LFP) has become a research hotspot in the field of lithium-ion battery cathode materials due to its excellent safety performance, environmental friendliness, and relatively stable cycle life, especially with broad application prospects in electric vehicles and energy storage systems. However, LFP materials have a significant drawback: the initial coulombic efficiency of rechargeable batteries made from them is relatively low. This is mainly because a solid electrolyte interphase (SEI) film forms on the negative electrode surface during the first charge and discharge process, consuming a certain amount of lithium ions and reducing the number of usable lithium ions. Furthermore, while the theoretical capacity of LFP is 170 mAh / g, in practical applications, the actual discharge capacity is often lower due to SEI film formation and losses from other side reactions. This limits the energy density and overall performance of LFP batteries, thus affecting their competitiveness in high-performance applications.
[0003] Therefore, improving the actual discharge capacity of lithium iron phosphate materials and the first coulombic efficiency of secondary batteries using lithium iron phosphate materials has become an important research direction for lithium iron phosphate materials. Summary of the Invention
[0004] In view of the technical problems existing in the background art, this application provides a composite lithium iron phosphate and its preparation method, positive electrode sheet and secondary battery, aiming to solve the technical problems of low actual discharge capacity of lithium iron phosphate material and low first coulombic efficiency of secondary battery using lithium iron phosphate material.
[0005] In a first aspect, embodiments of this application provide a composite lithium iron phosphate, which includes a core and a shell, with the shell covering at least a portion of the surface of the core;
[0006] The core comprises lithium iron phosphate particles in a lithium-deficient phase, and the shell comprises carbon material and lithium replenishing agent particles, with the carbon material coating at least a portion of the surface of the lithium replenishing agent particles.
[0007] In the technical solution of this application embodiment, by designing the structure of composite lithium iron phosphate, the core adopts lithium iron phosphate in the lithium-deficient phase to provide lithium vacancies. When composite lithium iron phosphate is applied to secondary batteries, part of the lithium released by the shell lithium replenishment agent is used to form SEI film, and part enters the lithium vacancies, which is beneficial to improve the discharge specific capacity, cycle performance and first coulombic efficiency of composite lithium iron phosphate when applied to secondary batteries.
[0008] In some embodiments, the average particle size of lithium iron phosphate particles in the lithium-deficient phase is 0.20 μm to 0.45 μm.
[0009] In this embodiment, the average particle size of lithium iron phosphate particles in the lithium-deficient phase is controlled to regulate the transport path of lithium ions in the composite lithium iron phosphate, which is beneficial to improve the extraction and insertion rate of lithium ions in the composite lithium iron phosphate, and enhance the charge specific capacity, discharge specific capacity and rate performance of the composite lithium iron phosphate.
[0010] In some embodiments, the average particle size of the lithium replenishing agent particles in the shell is 0.04 μm to 0.15 μm.
[0011] In this embodiment, controlling the average particle size of the lithium replenishing agent helps to facilitate the timely release of lithium ions from the lithium replenishing agent, making it easier for the composite lithium iron phosphate to provide lithium ions for the formation of the SEI film when applied to secondary batteries, thereby improving the first coulombic efficiency and cycle performance of the composite lithium iron phosphate when applied to secondary batteries.
[0012] In some embodiments, the average thickness of the carbon material is 2 nm to 10 nm.
[0013] In this embodiment, the average thickness of the carbon material is controlled. While utilizing the protective effect of the carbon material on the core, the transport path of lithium ions in the composite lithium iron phosphate is adjusted. This helps to maintain the high charging and discharging performance of the composite lithium iron phosphate, while maintaining the charge-discharge stability of the composite lithium iron phosphate and extending its service life when used in secondary batteries.
[0014] In some embodiments, the carbon material is at least one of graphite, graphene, carbon nanotubes, carbon nanofibers, and amorphous carbon.
[0015] In this embodiment, the above-mentioned selection of carbon materials is beneficial to effectively improve the conductivity of the composite lithium iron phosphate and enhance the stability of its charge-discharge performance.
[0016] In some embodiments, the mass fraction of carbon in the composite lithium iron phosphate is 1.3% to 3.3%.
[0017] In this embodiment, controlling the mass fraction of carbon in the composite lithium iron phosphate within the above-mentioned range helps the carbon material to be uniformly coated on the core surface, reduces the resistance of the composite lithium iron phosphate, and provides a smooth path for lithium ion insertion and extraction. This helps protect the core and the lithium replenishing agent, maintain the performance stability of the composite lithium iron phosphate, and improve the rate performance of the composite lithium iron phosphate.
[0018] In some embodiments, the chemical formula of lithium iron phosphate in the lithium-deficient phase is Li x FePO4, where x is 0.85~0.98.
[0019] In this embodiment, by selecting the type of lithium iron phosphate in the lithium-deficient phase, the lithium iron phosphate in the lithium-deficient phase provides an appropriate amount of lithium vacancies, which is beneficial for improving the cycle performance of the composite lithium iron phosphate while maintaining a high discharge specific capacity.
[0020] In some embodiments, the molar ratio of lithium iron phosphate in the lithium-deficient phase to the lithium replenishing agent is 1:(0.015~0.07).
[0021] In this embodiment, controlling the molar ratio of lithium iron phosphate in the lithium-deficient phase to the lithium replenishing agent helps to balance the initial coulombic efficiency, discharge specific capacity, and cycle performance of the composite lithium iron phosphate.
[0022] In some embodiments, the peak intensity of peak D in the Raman spectrum of the composite lithium iron phosphate is I. D The peak intensity of peak G is I G I D / I G The value is 0.65~0.8.
[0023] In this embodiment, for I D / I G By controlling the degree of graphitization of the carbon material in the shell, the conductivity of the composite lithium iron phosphate and its wetting effect with the electrolyte when applied to secondary batteries can be balanced, which helps to improve the electrochemical performance of secondary batteries.
[0024] In some embodiments, the specific surface area of the composite lithium iron phosphate is 9.0 m². 2 / g~15.0m 2 / g.
[0025] In this embodiment, the specific surface area of the composite lithium iron phosphate is controlled, which helps to improve the processing performance of the composite lithium iron phosphate and enhances the wetting effect of the composite lithium iron phosphate with the electrolyte when applied to secondary batteries, thereby helping to improve the electrochemical performance of secondary batteries.
[0026] In some embodiments, the compaction density of the composite lithium iron phosphate is 2.1 g / mL to 2.6 g / mL.
[0027] In this embodiment, controlling the compaction density of the composite lithium iron phosphate within the above-mentioned range helps to improve the energy density of the composite lithium iron phosphate used in secondary batteries and optimize the charge and discharge rate.
[0028] In some embodiments, the tap density of the composite lithium iron phosphate is 0.85 g / mL to 1.50 g / mL.
[0029] In this embodiment, controlling the tap density of the composite lithium iron phosphate within the above-mentioned range helps to improve the volumetric energy density of the composite lithium iron phosphate, improve the contact between composite lithium iron phosphate particles, reduce the gap between composite lithium iron phosphate particles, reduce the internal resistance of composite lithium iron phosphate when applied to secondary batteries, and improve the cycle stability and charge-discharge efficiency of composite lithium iron phosphate when applied to secondary batteries.
[0030] In some embodiments, the lithium supplement is Li3N.
[0031] In this embodiment, the selection of the lithium replenishing agent as described above effectively compensates for the lithium loss of composite lithium iron phosphate during the secondary battery cycle. While improving the discharge specific capacity, cycle performance and first coulombic efficiency of composite lithium iron phosphate when applied to secondary batteries, the products of the lithium replenishing agent after lithium ion removal are not easily left behind, thus avoiding the adverse effects of the residue of the lithium replenishing agent after lithium replenishment on the secondary battery using composite lithium iron phosphate.
[0032] Secondly, embodiments of this application provide a method for preparing composite lithium iron phosphate, comprising the following steps:
[0033] The first lithium source, phosphorus source, iron source, and first carbon source undergo a first mixing process to obtain a first mixture;
[0034] The first mixture is then subjected to pulping treatment to obtain a pulped material;
[0035] The slurry is subjected to a first calcination treatment under a protective atmosphere to obtain a first calcined product;
[0036] The second lithium source and the second carbon source are subjected to a second mixing process to obtain a second mixture;
[0037] The first calcined product is mixed with the second mixture to obtain a third mixture;
[0038] The third mixture is subjected to a second calcination treatment under nitrogen or an inert atmosphere to obtain the composite lithium iron phosphate.
[0039] The composite lithium iron phosphate includes a core and a shell, with the shell covering at least a portion of the surface of the core. The core includes lithium iron phosphate in a lithium-deficient phase, and the shell includes carbon material and a lithium replenishing agent, with the carbon material covering at least a portion of the surface of the lithium replenishing agent.
[0040] In the technical solution of this application embodiment, the lithium replenishing agent in the shell helps improve the initial capacity of the composite lithium iron phosphate, thereby increasing the first coulombic efficiency of the composite lithium iron phosphate. Furthermore, the lithium ions provided by the lithium replenishing agent in the shell replenish the lithium vacancies in the lithium-deficient phase of the core lithium iron phosphate, which is beneficial to improving the cycling performance of the composite lithium iron phosphate. The carbon material in the shell effectively protects the core and the lithium replenishing agent in the shell, which is beneficial to improving the cycling stability of the composite lithium iron phosphate.
[0041] In some embodiments, the temperature of the first calcination treatment is 500°C to 900°C, and the time of the first calcination treatment is 2h to 8h.
[0042] In this embodiment, a first mixture formed by a first lithium source, a phosphorus source, an iron source, and a first carbon source is slurried to form a slurry. The slurry is then subjected to a first calcination treatment to obtain a first calcination product. The first calcination product includes the core of a composite lithium iron phosphate. By controlling the conditions of the first calcination treatment, the stability of the core can be improved, thereby enhancing the performance stability of the composite lithium iron phosphate.
[0043] In some embodiments, the temperature of the second calcination treatment is 350°C to 700°C, and the time of the second calcination treatment is 0.5h to 4h.
[0044] In this embodiment, the second lithium source and the second carbon source form a second mixture. The second mixture is mixed with the first calcination product and then subjected to a second calcination treatment to form a composite lithium iron phosphate. Controlling the conditions of the second calcination treatment helps the shell layer to coat at least part of the surface of the core, improves the structural stability of the composite lithium iron phosphate, and thus improves the electrochemical performance of the composite lithium iron phosphate.
[0045] In some embodiments, the step of obtaining a first mixture by first mixing treatment of the first lithium source, phosphorus source, iron source and first carbon source includes: mixing the first lithium source, phosphorus source, iron source and first carbon source and then pulverizing them until the D50 particle size of the solid particles is 3μm~8μm to obtain the first mixture.
[0046] In this embodiment, by regulating the D50 particle size of the first mixture, it is helpful to control the particle size of the composite lithium iron phosphate core, regulate the transport path of lithium ions in the composite lithium iron phosphate, improve the extraction and insertion rate of lithium ions in the composite lithium iron phosphate, and enhance the charge specific capacity, discharge specific capacity and rate performance of the composite lithium iron phosphate.
[0047] In some embodiments, the molar ratio of lithium, phosphorus and iron in the first mixture is (0.85~0.98):1:1.
[0048] In this embodiment, controlling the molar ratio of the above three elements helps to obtain a specific type of lithium iron phosphate phase, thereby providing an appropriate amount of lithium vacancies, which is beneficial for improving the cycle performance of composite lithium iron phosphate while maintaining a high discharge specific capacity.
[0049] In some embodiments, the first lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, and lithium phosphate.
[0050] In this embodiment, the first lithium source has good reactivity, good processing performance, and is easy to obtain, making it suitable for industrial applications.
[0051] In some embodiments, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, ferric phosphate, and diammonium hydrogen phosphate.
[0052] In this embodiment, the phosphorus source has good reactivity, is widely available, and is easy to prepare lithium iron phosphate with a stable crystal structure in the lithium-deficient phase.
[0053] In some embodiments, the iron source includes at least one of ferrous oxalate, ferrous phosphate, ferrous sulfate, and ferrous chloride.
[0054] In this embodiment, selecting the type of iron source helps to form a stable lithium-deficient phase lithium iron phosphate, thereby improving the structural stability of the composite lithium iron phosphate.
[0055] In some embodiments, the first carbon source includes at least one of glucose, starch, polyvinyl alcohol, citric acid, urea, graphite, graphene, and carbon nanotubes.
[0056] In this embodiment, selecting the type of the first carbon source is beneficial for forming a uniform shell on the core surface, reducing the resistance of the composite lithium iron phosphate, and providing a smooth path for lithium ion insertion and extraction. This helps protect the core and the lithium replenishing agent, maintain the performance stability of the composite lithium iron phosphate, and improve the rate performance of the composite lithium iron phosphate.
[0057] In some embodiments, the mass fraction of carbon in the first calcination product is 2.2% to 2.4%.
[0058] In this embodiment, by controlling the mass fraction of carbon in the first calcination product, it is helpful for the carbon material to be uniformly coated on the core surface, which is beneficial to improving the rate performance of the composite lithium iron phosphate and extending the cycle life of the composite lithium iron phosphate.
[0059] In some embodiments, the mass ratio of the second lithium source to the second carbon source is (5~10):1.
[0060] In this embodiment, controlling the mass ratio of the second lithium source and the second carbon source within the above-mentioned range helps to passivate the second lithium source using the second carbon source, improves the stability of the second mixture formed by the second lithium source and the second carbon source in the second calcination treatment, thereby improving the structural stability and performance stability of the composite lithium iron phosphate.
[0061] In some embodiments, the second lithium source includes at least one of lithium powder and lithium nitride.
[0062] In this embodiment, the second lithium source is selected, and the resulting lithium replenishing agent can effectively replenish lithium while avoiding the adverse effects of the residue of the lithium replenishing agent after lithium replenishment on the secondary battery using composite lithium iron phosphate.
[0063] In some embodiments, the second carbon source includes at least one of bitumen and paraffin.
[0064] In this embodiment, at least one of asphalt and paraffin is selected as the second carbon source, which is beneficial for passivating the second lithium source. Furthermore, the high viscosity of asphalt and paraffin helps to better fix them to the core surface, thereby improving the structural and chemical stability of the composite lithium iron phosphate.
[0065] In some embodiments, the second lithium source is lithium powder and the second carbon source is asphalt. The second lithium source and the second carbon source are mixed and heated until the asphalt softens. After mixing, the mixture is cooled until the asphalt solidifies to obtain a second mixture.
[0066] In this embodiment, when the second lithium source is lithium powder and the second carbon source is asphalt, the above-mentioned mixing method results in a more uniform mixture of the second lithium source and the second carbon source. This helps the second carbon source to fully encapsulate and passivate the second lithium source, improves the stability of the second mixture formed by the second lithium source and the second carbon source in the second calcination process, and reduces the contact between the formed lithium replenishing agent and external moisture. At the same time, the high viscosity of asphalt is used to better fix it to the core surface, effectively improving the structural stability and performance stability of the composite lithium iron phosphate.
[0067] In some embodiments, the second lithium source is lithium powder, the second carbon source is pitch, and the third mixture is subjected to a second calcination treatment under a nitrogen atmosphere.
[0068] In this embodiment, the second calcination under a nitrogen atmosphere is beneficial for the in-situ formation of lithium nitride supplementation agent, thereby improving the structural stability of the composite lithium iron phosphate.
[0069] Thirdly, embodiments of this application provide a positive electrode sheet, including a current collector and a positive electrode active material, a conductive agent, and a binder located on one or both sides of the current collector; the positive electrode active material is the composite lithium iron phosphate in the above embodiments of this application, or is a composite lithium iron phosphate prepared by the preparation method in the above embodiments.
[0070] In this embodiment, the positive electrode contains the aforementioned composite lithium iron phosphate, thus exhibiting excellent electrochemical performance.
[0071] Fourthly, embodiments of this application provide a secondary battery, which includes a positive electrode, a negative electrode, and a separator.
[0072] In this embodiment, the secondary battery includes the positive electrode sheet as described in the above embodiment, thus having the advantages of high capacity, high coulombic efficiency, and good cycle performance.
[0073] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0074] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0075] Figure 1 This is a TEM image of the composite lithium iron phosphate in Example 1 of this application.
[0076] Figure 2 This is a flowchart illustrating the preparation process of composite lithium iron phosphate in one embodiment of this application.
[0077] Figure 3 This is a SEM image of the composite lithium iron phosphate in Example 1 of this application. Detailed Implementation
[0078] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0079] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0080] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0081] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0082] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0083] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).
[0084] In the description of the embodiments of this application, unless otherwise specified, "ppm" means the mass of the tested element, molecule or ion in parts per million of the sample mass.
[0085] In the description of the embodiments of this application, unless otherwise specified, the water used in the pulping process is selected from at least one of deionized water, distilled water, recycled water, pure water, and ultrapure water.
[0086] In the description of the embodiments of this application, unless otherwise specified, "content" refers to the mass percentage of the tested element, molecule or ion in the sample.
[0087] The theoretical specific capacity of lithium iron phosphate is 170 mAh / g, but its actual specific capacity is usually lower, which limits the energy density and overall performance of lithium iron phosphate batteries and affects their application range.
[0088] To address the aforementioned technical problems of lithium iron phosphate materials, this application provides a composite lithium iron phosphate, its preparation method, a positive electrode, and a secondary battery. The composite lithium iron phosphate uses lithium iron phosphate in a lithium-deficient phase as its core, providing a large number of lithium vacancies. During charging and discharging, lithium ions in the shell-layer lithium replenishment agent are used to form an SEI film, partially filling the lithium vacancies in the lithium-deficient phase lithium iron phosphate, thereby improving the initial coulombic efficiency and capacity of the composite lithium iron phosphate. Furthermore, coating at least part of the lithium replenishment agent with carbon material in the shell helps improve the stability of the lithium replenishment agent, reducing failure caused by contact with the external environment, and improving the lithium replenishment performance of the agent. Consequently, the capacity and initial coulombic efficiency of the positive electrode and the secondary battery are also improved.
[0089] The electrical devices provided in this application embodiment can be, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Among them, electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0090] Firstly, such as Figure 1 As shown, this application provides a composite lithium iron phosphate, which includes a core and a shell, with the shell covering at least a portion of the surface of the core;
[0091] The core comprises lithium iron phosphate particles in a lithium-deficient phase, and the shell comprises carbon material and lithium replenishing agent particles, with the carbon material coating at least a portion of the surface of the lithium replenishing agent particles.
[0092] In the technical solution of this application embodiment, "core including lithium iron phosphate particles with lithium deficiency phase" means that the core includes lithium iron phosphate particles with lithium deficiency phase (primary particles) and / or aggregates of lithium iron phosphate particles with lithium deficiency phase (secondary particles). "Lithium replenishing particles" refers to primary lithium replenishing particles. By designing the structure of the composite lithium iron phosphate, the core is protected by a shell, reducing direct contact between the lithium iron phosphate particles with lithium deficiency phase and the electrolyte. The core uses lithium iron phosphate with lithium deficiency phase to provide lithium vacancies. When the lithium replenishing agent releases lithium ions in the shell, some lithium ions participate in the formation of the SEI film, and some lithium ions effectively fill the lithium vacancies provided by the lithium iron phosphate particles with lithium deficiency phase, reducing irreversible loss of lithium ions during charging and discharging, thereby improving the first coulombic efficiency of the composite lithium iron phosphate when applied to a secondary battery and improving the discharge capacity of the composite lithium iron phosphate. In addition, the carbon material in the shell plays a role in protecting the lithium replenishing agent and improving the stability of the composite lithium iron phosphate. On the other hand, it helps to improve the electronic conductivity of the composite lithium iron phosphate, thereby improving the overall conductivity of the secondary battery and helping to improve the power characteristics of the secondary battery.
[0093] When the composite lithium iron phosphate in this embodiment is applied to a secondary battery at 25°C, the specific capacity at 0.2C initial charge can reach 160mAh / g~170mAh / g, the specific capacity at 0.2C initial discharge can reach 155mAh / g~165mAh / g, the initial coulombic efficiency at 0.2C can reach 96%~99.5%, the specific capacity at 1C initial charge can reach 150mAh / g~158mAh / g, the initial discharge specific capacity at 1C can reach 142mAh / g~153mAh / g, the initial coulombic efficiency at 1C can reach 94%~99%, and the discharge capacity retention rate after 1000 cycles at 1C can reach 97%~99%, exhibiting good capacity, rate performance, and cycle stability.
[0094] Further, in some embodiments, the average particle size of the lithium-deficient lithium iron phosphate particles is 0.20 μm to 0.45 μm. Specifically, but not limitingly, the average particle size of the lithium-deficient lithium iron phosphate particles is 0.20 μm, 0.23 μm, 0.25 μm, 0.27 μm, 0.30 μm, 0.33 μm, 0.35 μm, 0.38 μm, 0.40 μm, 0.42 μm, 0.45 μm, or any value within the range of any two of the above values. Even more specifically, the average particle size of the lithium-deficient lithium iron phosphate particles is 0.23 μm to 0.30 μm.
[0095] In the technical solution of this application embodiment, the average particle size of lithium iron phosphate particles in the lithium-deficient phase refers to the average particle size of the primary particles of lithium iron phosphate in the lithium-deficient phase, also known as the average primary particle size of lithium iron phosphate particles in the lithium-deficient phase. Controlling the average primary particle size of lithium iron phosphate particles in the lithium-deficient phase within the above range provides an appropriate transport path, which is beneficial to improving the rate of lithium ion extraction and insertion in the composite lithium iron phosphate, thereby improving the charge specific capacity, discharge specific capacity and rate performance of the composite lithium iron phosphate. On the other hand, a reasonable particle size is beneficial to reduce the stress between lithium iron phosphate particles in the lithium-deficient phase, thereby reducing particle damage during cycling and improving the cycle stability of the composite lithium iron phosphate.
[0096] Further, in some embodiments, the average particle size of the lithium replenishing agent particles in the shell layer is 0.04 μm to 0.15 μm. Specifically, but not limitingly, the average particle size of the lithium replenishing agent particles is 0.04 μm, 0.06 μm, 0.08 μm, 0.10 μm, 0.12 μm, 0.15 μm, or any value within the range of any two of the above values. Even more specifically, the average particle size of the lithium replenishing agent particles is 0.04 μm to 0.06 μm.
[0097] In the technical solution of this application embodiment, the average particle size of the lithium replenishing agent particles refers to the average particle size of the primary particles of the lithium replenishing agent, also known as the average primary particle size of the lithium replenishing agent particles. Controlling the average primary particle size of the lithium replenishing agent particles within the above range helps to facilitate the timely release of lithium ions from the lithium replenishing agent, making it easier for the composite lithium iron phosphate to provide lithium ions for the formation of the SEI film when applied to secondary batteries, and to promptly enter the lithium vacancies provided by the lithium-deficient phase lithium iron phosphate, thereby improving the first coulombic efficiency, discharge specific capacity and cycle performance of the composite lithium iron phosphate when applied to secondary batteries; at the same time, it also helps to improve the dispersibility of the lithium replenishing agent in carbon materials, so that the lithium ions in the lithium replenishing agent are released uniformly, thereby improving the structural stability and cycle performance of the composite lithium iron phosphate.
[0098] Furthermore, in some embodiments, the average thickness of the carbon material is 2 nm to 10 nm. Specifically, but not limitingly, the average thickness of the carbon material is 2 nm, 3 nm, 5 nm, 8 nm, 10 nm, or any value within the range of any two of the above values.
[0099] In the technical solution of this application embodiment, the average thickness of the carbon material refers to the average thickness of the shell after the lithium replenishment agent is removed. Controlling the average thickness of the carbon material within the above range helps to fully protect the lithium-deficient lithium iron phosphate core and improve the service life of the composite lithium iron phosphate. On the other hand, it helps to adjust the lithium ion transport path, improve the charge and discharge efficiency of the secondary battery, maintain the charge-discharge stability of the composite lithium iron phosphate, and extend the service life of the composite lithium iron phosphate when used in secondary batteries.
[0100] Furthermore, in some embodiments, the carbon material is at least one of graphite, graphene, carbon nanotubes, carbon nanofibers, and amorphous carbon.
[0101] In the technical solutions of this application embodiment, carbon materials all possess excellent electrical conductivity. Specifically, the layered structure of graphite, the two-dimensional planar structure of graphene, the tubular structure of carbon nanotubes, and the fibrous structure of carbon nanofibers provide abundant transport channels for lithium ions, facilitating rapid insertion and extraction of lithium ions, thereby improving the charge and discharge rate of the secondary battery. Amorphous carbon possesses microporous and mesoporous structures, which facilitate the adsorption of some of the gases generated during the reaction, reducing the gas pressure inside the battery and improving safety. Furthermore, the aforementioned carbon materials effectively coat the lithium replenishing agent, regulating the lithium ion release rate within the agent, thereby contributing to improved structural stability of the composite lithium iron phosphate.
[0102] Further, in some embodiments, the mass fraction of carbon in the composite lithium iron phosphate is 1.3% to 3.3%. Specifically, but not limitingly, the mass fraction of carbon in the composite lithium iron phosphate is 1.3%, 1.5%, 1.55%, 1.6%, 1.7%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.3%, or any value within the range of any two of the above values. Even further, the mass fraction of carbon in the composite lithium iron phosphate is 1.54% to 2.89%.
[0103] In the technical solution of this application embodiment, an appropriate amount of carbon elements forms a continuous conductive network, significantly reducing the electron transfer resistance between the particles of the composite lithium iron phosphate, thereby improving the overall conductivity of the composite lithium iron phosphate and helping to improve its rate performance. Furthermore, controlling the carbon element content within the aforementioned range is beneficial for forming a uniform shell, protecting the core and lithium supplementer, and maintaining the performance stability of the composite lithium iron phosphate.
[0104] Furthermore, in some embodiments, the lithium-deficient phase lithium iron phosphate has the chemical formula Li. x FePO4, where x is 0.85 to 0.98. Specifically, but not limitingly, x is any value within the range of 0.85, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, or any two of the above values. More specifically, x is 0.9 to 0.95.
[0105] In the technical solution of this application embodiment, the lithium iron phosphate core-deficient phase provides an appropriate amount of lithium vacancies, allowing lithium ions from the lithium replenishment agent to be rapidly inserted, thereby improving the discharge capacity of the composite lithium iron phosphate and the first coulombic efficiency when applied to secondary batteries, and enhancing the cycle performance of the composite lithium iron phosphate.
[0106] Further, in some embodiments, the molar ratio of lithium iron phosphate in the lithium-deficient phase to the lithium replenishing agent is 1:(0.015~0.07). Specifically, but not limitingly, the molar ratio of lithium iron phosphate in the lithium-deficient phase to the lithium replenishing agent is 1:0.015, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, or any value within the range of any two of the above ratios. Even further, the molar ratio of lithium iron phosphate in the lithium-deficient phase to the lithium replenishing agent is 1:(0.03~0.05).
[0107] In the technical solution of this application embodiment, controlling the molar ratio of lithium iron phosphate in the lithium-deficient phase and the lithium replenishing agent within the above range not only compensates for the lithium ions lost during the formation of the SEI film during the first charging process and fully fills the lithium vacancies in the lithium iron phosphate in the lithium-deficient phase, but also helps to avoid the formation of lithium dendrites or unnecessary side reactions due to excess lithium replenishing agent, thereby improving the cycle stability and coulombic efficiency of composite lithium iron phosphate when applied to secondary batteries.
[0108] Furthermore, in some embodiments, the peak intensity of peak D in the Raman spectrum of the composite lithium iron phosphate is I. D The peak intensity of peak G is I G I D / I G The value is 0.65~0.8. Specific, but not limiting, I D / I G It is any value within the range of 0.65, 0.68, 0.71, 0.74, 0.77, 0.8, or any two of the above values. Furthermore, I... D / I G The value is 0.71~0.78.
[0109] In the technical solution of this application embodiment, peak D is located at 1350±10 cm⁻¹ in the Raman spectrum. -1At this location, used to characterize the defects in the carbon material of the shell, the G peak is located at 1580±10 cm⁻¹ in the Raman spectrum. -1 At this location, the degree of graphitization of the carbon material in the shell is used to characterize I. D / I G Controlling the intensity ratio of the D peak and the G peak in the Raman spectrum within the above range helps to balance the conductivity of the composite lithium iron phosphate while improving the wettability of the composite lithium iron phosphate to the electrolyte, increasing the lithium ion transport rate, and thus improving the rate performance and discharge specific capacity of the secondary battery.
[0110] Furthermore, in some embodiments, the specific surface area of the composite lithium iron phosphate is 9.0 m². 2 / g~15.0m 2 / g. Specifically, but not limitingly, the specific surface area of the composite lithium iron phosphate is 9.0 m². 2 / g, 9.5m 2 / g, 10.0m 2 / g, 10.5m 2 / g, 11.0m 2 / g, 11.5m 2 / g, 12.0m 2 / g, 12.5m 2 / g, 13.0m 2 / g, 13.5m 2 / g、14m 2 / g, 14.5m 2 / g, 15.0m 2 / g or any value within the range of any two of the above values. Furthermore, the specific surface area of the composite lithium iron phosphate is 10.0 m². 2 / g~15.0m 2 / g.
[0111] In the technical solution of this application embodiment, controlling the specific surface area of the composite lithium iron phosphate within the above-mentioned range helps to improve the wetting effect of the composite lithium iron phosphate with the electrolyte when it is applied to secondary batteries, improve the charge and discharge efficiency, discharge specific capacity and rate performance of the composite lithium iron phosphate, and help to improve the processing performance of the composite lithium iron phosphate.
[0112] Furthermore, in some embodiments, the compaction density of the composite lithium iron phosphate is 2.1 g / mL to 2.6 g / mL. Specifically, but not limitingly, the compaction density of the composite lithium iron phosphate is 2.1 g / mL, 2.15 g / mL, 2.2 g / mL, 2.25 g / mL, 2.3 g / mL, 2.35 g / mL, 2.4 g / mL, 2.45 g / mL, 2.5 g / mL, 2.55 g / mL, and 2.6 g / mL. Even more specifically, the compaction density of the composite lithium iron phosphate is 2.25 g / mL to 2.55 g / mL.
[0113] In the technical solution of this application embodiment, the compaction density of the composite lithium iron phosphate is controlled. On the one hand, this improves the energy density of the composite lithium iron phosphate in secondary batteries and expands its application range. On the other hand, it helps to achieve more sufficient contact between the composite lithium iron phosphate particles, reduces the internal resistance of the composite lithium iron phosphate, and reduces the energy loss of the composite lithium iron phosphate during the charge-discharge process. Furthermore, the compact structure improves the problem of particle breakage and shedding of the composite lithium iron phosphate during the charge-discharge process, enhances the mechanical stability of the positive electrode sheet using this composite lithium iron phosphate, thereby improving the cycle stability of the secondary battery and extending its service life.
[0114] Further, in some embodiments, the tap density of the composite lithium iron phosphate is 0.85 g / mL to 1.50 g / mL. Specifically, but not limitingly, the tap density of the composite lithium iron phosphate is any value within the range of 0.85 g / mL, 0.90 g / mL, 0.95 g / mL, 1.0 g / mL, 1.10 g / mL, 1.15 g / mL, 1.20 g / mL, 1.30 g / mL, 1.40 g / mL, 1.50 g / mL, or any combination of two of the above values. Even more specifically, the tap density of the composite lithium iron phosphate is 0.90 g / mL to 1.40 g / mL.
[0115] In the technical solution of this application embodiment, controlling the tap density of composite lithium iron phosphate helps to reduce the gaps between particles, reduce the contact resistance inside the secondary battery, reduce the internal resistance of composite lithium iron phosphate when applied to the secondary battery, and thus improve the charge-discharge efficiency of composite lithium iron phosphate when applied to the secondary battery; it also helps to make the composite lithium iron phosphate more compact, reduce the air content inside the battery, and thus improve the cycle stability of the secondary battery.
[0116] Furthermore, in some embodiments, the lithium replenishing agent is Li3N.
[0117] In the technical solution of this application embodiment, the selection of the above-mentioned lithium replenishing agent effectively compensates for the lithium ions consumed during the initial charging process due to the formation of the SEI film and the lithium loss of the composite lithium iron phosphate during cycling, significantly improving the discharge specific capacity, initial coulombic efficiency, and cycle performance of the composite lithium iron phosphate when applied to secondary batteries. Furthermore, the products of the above-mentioned lithium replenishing agent after lithium ion removal are not easily left behind, avoiding adverse effects of the residue of the lithium replenishing agent after lithium replenishment on the secondary battery using composite lithium iron phosphate.
[0118] like Figure 2 As shown, in a second aspect, embodiments of this application provide a method for preparing composite lithium iron phosphate, comprising the following steps:
[0119] The first lithium source, phosphorus source, iron source, and first carbon source undergo a first mixing process to obtain a first mixture;
[0120] The first mixture is then subjected to pulping treatment to obtain a pulped material;
[0121] The slurry is subjected to a first calcination treatment under a protective atmosphere to obtain a first calcined product;
[0122] The second lithium source and the second carbon source are subjected to a second mixing process to obtain a second mixture;
[0123] The first calcined product is mixed with the second mixture to obtain a third mixture;
[0124] The third mixture is subjected to a second calcination treatment under nitrogen or an inert atmosphere to obtain the composite lithium iron phosphate.
[0125] The composite lithium iron phosphate includes a core and a shell, with the shell covering at least a portion of the surface of the core. The core includes lithium iron phosphate in a lithium-deficient phase, and the shell includes carbon material and a lithium replenishing agent, with the carbon material covering at least a portion of the surface of the lithium replenishing agent.
[0126] Adding a first carbon source to the first mixture helps form a preliminary carbon coating layer on the surface of the lithium iron phosphate core in the lithium-deficient phase, which is beneficial to improving the conductivity of the composite lithium iron phosphate. Preparing a second mixture with a second lithium source and a second carbon source is beneficial to forming a shell structure of carbon material coating the lithium replenishing agent after secondary calcination, which further improves the conductivity of the composite lithium iron phosphate while effectively protecting the lithium replenishing agent in the core and shell, thus improving the stability of the composite lithium iron phosphate. On the other hand, the lithium replenishing agent in the shell provides some lithium ions to replenish the lithium vacancies in the lithium-deficient phase lithium iron phosphate in the core, and some lithium ions participate in the formation of the SEI film, which helps to improve the discharge specific capacity, first coulombic efficiency and cycle performance of the composite lithium iron phosphate.
[0127] Furthermore, in some embodiments, the temperature of the first calcination treatment is 500℃~900℃, and the time of the first calcination treatment is 2h~8h; specifically, the temperature of the first calcination treatment is any value within the range of 500℃, 600℃, 650℃, 700℃, 750℃, 800℃, 900℃ or any two of the above values, without special limitation; the temperature of the first calcination treatment is any value within the range of 2h, 3h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h or any two of the above values, without special limitation.
[0128] In the technical solution of this application embodiment, a first mixture formed by a first lithium source, a phosphorus source, an iron source, and a first carbon source is slurried to form a slurry. The slurry is then subjected to a first calcination treatment to obtain a first calcination product. The first calcination product includes the core of a composite lithium iron phosphate. Controlling the conditions of the first calcination treatment is beneficial to forming a uniform carbon coating layer on the surface of the lithium iron phosphate phase in the core, stabilizing the structure of the core, and making the average particle size of the core fall within the range of 0.20μm to 0.45μm, thereby improving the performance stability of the composite lithium iron phosphate.
[0129] Furthermore, in some embodiments, the heating rate of the first calcination treatment is 50°C / h to 150°C / h. Specifically, but not limitingly, the heating rate of the first calcination treatment is 50°C / h, 60°C / h, 70°C / h, 80°C / h, 90°C / h, 100°C / h, 110°C / h, 120°C / h, 130°C / h, 140°C / h, or 150°C / h.
[0130] In the technical solution of this application embodiment, controlling the heating rate of the first calcination treatment helps to fully remove moisture from the slurry, so that the slurry is heated evenly inside, thereby improving the structural stability of the first calcination product.
[0131] Furthermore, in some embodiments, the protective atmosphere includes at least one of nitrogen and an inert gas, wherein the inert gas includes at least one of argon, helium, and neon.
[0132] In the technical solution of this application embodiment, performing the first calcination treatment under the above-mentioned protective atmosphere helps to improve the purity of the first calcination product and improve the uniformity of the carbon coating layer on the surface of lithium iron phosphate in the lithium-deficient phase.
[0133] Furthermore, in some embodiments, the temperature of the second calcination treatment is 350℃~700℃, and the time of the second calcination treatment is 1h~3h; specifically, the temperature of the second calcination treatment is 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 700℃, or any value within the range of any two of the above values, without any special limitation; the time of the second calcination treatment is 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 4h, or any value within the range of any two of the above values, without any special limitation.
[0134] In the technical solution of this application embodiment, a second lithium source and a second carbon source form a second mixture. The second mixture is mixed with the first calcination product and then subjected to a second calcination treatment to form a composite lithium iron phosphate. Controlling the conditions of the second calcination treatment helps to improve the I... D / I G The value falls within the range of 0.65 to 0.8, thereby ensuring that the composite lithium iron phosphate has appropriate conductivity while improving the wettability of the composite lithium iron phosphate to the electrolyte, increasing the lithium ion transport rate, and thus improving the rate performance and discharge specific capacity of the secondary battery and other electrochemical performance.
[0135] Furthermore, in some embodiments, the heating rate of the second calcination treatment is 50°C / h to 150°C / h. Specifically, but not limitingly, the heating rate of the second calcination treatment is 50°C / h, 60°C / h, 70°C / h, 80°C / h, 90°C / h, 100°C / h, 110°C / h, 120°C / h, 130°C / h, 140°C / h, or 150°C / h.
[0136] In the technical solution of this application embodiment, controlling the heating rate of the second calcination treatment helps to balance the preparation efficiency and the structural stability of the composite lithium iron phosphate, thereby helping to improve the electrochemical performance of the composite lithium iron phosphate.
[0137] Furthermore, in some embodiments, the step of obtaining a first mixture by first mixing treatment of the first lithium source, phosphorus source, iron source and first carbon source includes: mixing the first lithium source, phosphorus source, iron source and first carbon source and then pulverizing them until the D50 particle size of the solid particles is 3μm~8μm to obtain the first mixture.
[0138] In the technical solution of this application embodiment, regulating the D50 particle size of the first mixture helps to ensure uniform particle size of the first calcined product obtained by sintering, resulting in a composite lithium iron phosphate core with a suitable particle size. Regulating the transport path of lithium ions in the composite lithium iron phosphate is beneficial to improving the rate of lithium ion extraction and insertion in the composite lithium iron phosphate, thereby enhancing the charge specific capacity, discharge specific capacity, and rate performance of the composite lithium iron phosphate. Furthermore, controlling the D50 particle size within the above range enables the composite lithium iron phosphate to have a higher compaction density, thereby improving the energy density of the secondary battery.
[0139] Furthermore, in some embodiments, the molar ratio of lithium, phosphorus, and iron in the first mixture is (0.85~0.98):1:1; specifically, the molar ratio of lithium, phosphorus, and iron is 0.85:1:1, 0.9:1:1, 0.91:1:1, 0.92:1:1, 0.93:1:1, 0.94:1:1, 0.95:1:1, 0.98:1:1, or any value within the range of any two of the above ratios, without any special limitation herein.
[0140] In the technical solution of this application embodiment, adjusting the molar ratio of the above three elements helps to obtain a specific type of lithium iron phosphate phase, thereby providing an appropriate amount of lithium vacancies, which is beneficial for improving the cycle performance of composite lithium iron phosphate while maintaining a high discharge specific capacity.
[0141] Furthermore, in some embodiments, the first lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, and lithium phosphate.
[0142] In the technical solution of this application embodiment, the first lithium source has good reactivity, good processing performance, and is easy to obtain, making it suitable for industrial applications. Furthermore, lithium carbonate and lithium nitrate are easily decomposed at high temperatures, providing lithium ions and promoting the formation of lithium iron phosphate, a lithium-deficient phase; lithium hydroxide has good stability, which facilitates more uniform mixing with other raw materials in the slurry; and lithium phosphate contains phosphorus, which can simultaneously provide lithium and phosphorus, simplifying the synthesis steps.
[0143] Furthermore, in some embodiments, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, ferric phosphate, and diammonium hydrogen phosphate.
[0144] In the technical solutions of this application embodiment, the aforementioned phosphorus source has good reactivity, is widely available, and is easy to prepare lithium iron phosphate with a stable crystal structure. Furthermore, phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate are low in cost; iron phosphate has high reactivity and does not introduce other impurities, which helps to form a purer lithium iron phosphate phase.
[0145] Furthermore, in some embodiments, the iron source includes at least one of ferrous oxalate, ferrous phosphate, ferrous sulfate, and ferrous chloride.
[0146] In the technical solution of this application embodiment, selecting the type of iron source helps to form a stable lithium-deficient phase lithium iron phosphate, thereby improving the structural stability of composite lithium iron phosphate.
[0147] Furthermore, the first carbon source includes at least one of glucose, starch, polyvinyl alcohol, citric acid, urea, graphite, graphene, and carbon nanotubes.
[0148] In the technical solutions of this application embodiment, organic carbon sources such as glucose, starch, polyvinyl alcohol, citric acid, and urea are low in cost and widely available. During the preparation process, they can be converted into high-quality carbon to form a conductive network, enhance the conductivity of the composite lithium iron phosphate, and thus improve the rate performance of the secondary battery. Graphene and carbon nanotubes also help to enhance the mechanical strength and structural stability of the composite lithium iron phosphate. Graphite forms a porous structure during calcination, which is conducive to the rapid diffusion of lithium ions and also helps to improve the rate performance of the composite lithium iron phosphate in secondary batteries.
[0149] Furthermore, in some embodiments, after mixing the first lithium source, phosphorus source, iron source, and first carbon source, the pulverization process includes crushing with a crusher, grinding with a ball mill, rod mill, air jet mill, or other mills, crushing with a roller mill, or pulverizing with an ultrasonic pulverizer or air jet mill.
[0150] In the technical solution of this application embodiment, the mixture can be pulverized using the above-mentioned common pulverization method to obtain a first mixture with a D50 particle size of 3μm~8μm. Controlling the D50 particle size of the first mixture within the above range helps to obtain a composite lithium iron phosphate core with a suitable particle size, regulates the transport path of lithium ions in the composite lithium iron phosphate, and is beneficial to improve the extraction and insertion rate of lithium ions in the composite lithium iron phosphate, thereby improving the charge specific capacity, discharge specific capacity and rate performance of the composite lithium iron phosphate. Furthermore, controlling the D50 particle size of the first mixture within the above range helps to give the composite lithium iron phosphate a higher compaction density, thereby improving the energy density of the composite lithium iron phosphate when applied to secondary batteries.
[0151] Furthermore, in some embodiments, the method for pulping the first mixture is as follows: adding water in an amount of 0.15 to 0.3 times the total mass of the first mixture to the first mixture, stirring evenly to obtain a pulp.
[0152] In the technical solution of this application embodiment, controlling the conditions of slurry treatment helps to uniformly disperse the components in the first mixture, thereby making the component distribution of the first calcined product more uniform and improving the overall performance of the composite lithium iron phosphate.
[0153] Furthermore, in some embodiments, the mass fraction of carbon in the first calcined product is 2.2% to 2.4%. Specifically, but not limitingly, the mass fraction of carbon in the first calcined product is 2.2%, 2.25%, 2.28%, 2.30%, 2.33%, 2.34%, 2.38%, 2.4%, or any value within the range of any two of the above values, and is not specifically limited herein.
[0154] In the technical solution of this application embodiment, controlling the mass fraction of carbon in the first calcination product helps to initially form a conductive network structure on the surface of the lithium iron phosphate core in the lithium-deficient phase, thereby improving the electronic conductivity of the composite lithium iron phosphate.
[0155] Furthermore, in some embodiments, after the first calcination treatment is completed, the material is pulverized to a D50 particle size of 1μm to 3μm to obtain the first calcined product; specifically, the D50 particle size of the first calcined product is 1μm, 1.5μm, 2μm, 2.5μm, 3μm or any value within the range of any two of the above values, without any special limitation here.
[0156] In the technical solution of this application embodiment, by controlling the particle size of the first calcined product, it is helpful to obtain a core of the required size and to improve the coating effect of the shell on the core, thereby improving the conductivity of the composite lithium iron phosphate. It is also beneficial for the lithium ions in the shell lithium replenishing agent to fill the lithium vacancies in the lithium-deficient phase of the core lithium iron phosphate in a timely and sufficient manner.
[0157] Furthermore, in some embodiments, after the first calcination treatment, the method of pulverizing the material to a D50 particle size of 1μm~3μm includes grinding, crushing, rolling, shearing, air jet milling, ultrasonic milling, cryogenic milling, etc.
[0158] In the technical solution of this application embodiment, the above-mentioned pulverization method can efficiently obtain the first calcined product with a D50 particle size of 1μm to 3μm. Controlling the particle size of the first calcined product within the above range helps to obtain the core of the required size and helps to improve the coating effect of the shell on the core, thereby improving the conductivity of the composite lithium iron phosphate. It also helps the lithium ions in the shell lithium replenishment agent to fill the lithium vacancies in the lithium-deficient phase of lithium iron phosphate in the core in a timely and sufficient manner.
[0159] Furthermore, in some embodiments, the mass ratio of the second lithium source to the second carbon source is (5~10):1; specifically, the mass ratio of the second lithium source to the second carbon source is 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any value within the range formed by any two of the above ratios.
[0160] In the technical solution of this application embodiment, controlling the mass ratio of the second lithium source and the second carbon source helps to passivate the second lithium source using the second carbon source, improves the stability of the second mixture formed by the second lithium source and the second carbon source in the second calcination treatment, thereby improving the structural stability and performance stability of the composite lithium iron phosphate; on the other hand, it helps to ensure that lithium ions in the lithium replenishing agent are released steadily at an appropriate rate, thereby improving its long-term lithium replenishment performance.
[0161] Furthermore, in some embodiments, the second lithium source includes at least one of lithium powder and lithium nitride.
[0162] In the technical solutions of this application embodiment, the lithium replenishing agent prepared with the above-mentioned second lithium source can effectively replenish the lithium ions lost by the lithium iron phosphate in the lithium-deficient core phase during charging, thereby improving the discharge specific capacity and first coulombic efficiency of the composite lithium iron phosphate; and the lithium replenishing agent prepared with the above-mentioned second lithium source has less residue after lithium replenishment, which will not have an adverse effect on the secondary battery using composite lithium iron phosphate.
[0163] Furthermore, in some embodiments, the second carbon source includes at least one of bitumen and paraffin.
[0164] In the technical solution of this application embodiment, selecting at least one of asphalt and paraffin as the second carbon source is beneficial to passivating the second lithium source. Asphalt and paraffin have suitable viscosity. Selecting at least one of asphalt and paraffin as the second carbon source is also beneficial to improve the bonding force between the core and shell in the composite lithium iron phosphate, thereby improving the structural stability of the composite lithium iron phosphate.
[0165] Furthermore, in some embodiments, the second lithium source is lithium powder and the second carbon source is asphalt. The second lithium source and the second carbon source are mixed and heated until the asphalt softens. After mixing, the mixture is cooled until the asphalt solidifies to obtain a second mixture.
[0166] In the technical solution of this application embodiment, since lithium powder has high activity, asphalt forms a uniform and stable coating layer on the surface of lithium powder, which is beneficial to improving the chemical stability of the shell layer; it also helps to reduce the area of direct contact between the lithium replenishing agent and the electrolyte, thereby improving the cycle stability of the composite lithium iron phosphate; at the same time, the high viscosity of asphalt is used to better fix it to the core surface, effectively improving the structural stability and performance stability of the composite lithium iron phosphate.
[0167] Furthermore, in some embodiments, the asphalt is heated under vacuum until it softens.
[0168] In the technical solution of this application embodiment, controlling the heating conditions helps to reduce the impurity content and helps to coat the lithium powder with asphalt, thereby helping to form a shell layer of carbon material coating on at least part of the surface of the lithium supplement particles, which is beneficial to improving the structural stability of the shell layer and the performance stability of the composite lithium iron phosphate.
[0169] Furthermore, in some embodiments, the mixing process includes mechanical mixing, ultrasonic mixing, etc., wherein mechanical mixing includes mixing using equipment such as a mixer, a double cone mixer, or a V-type mixer.
[0170] In the technical solution of this application embodiment, the above-described method of mixing helps to improve the mixing rate, so that the second carbon source and the second lithium source are fully mixed, thereby helping to form a shell with uniform component distribution.
[0171] Furthermore, in some embodiments, the cooling method includes using cooling water for cooling.
[0172] In the technical solution of this application embodiment, cooling water is used for cooling, which has a fast cooling rate and does not affect the mixing effect.
[0173] Furthermore, in some embodiments, the second lithium source is lithium powder, the second carbon source is pitch, and the third mixture is subjected to a second calcination treatment under a nitrogen atmosphere.
[0174] In the technical solution of this application embodiment, the second calcination under a nitrogen atmosphere is conducive to the in-situ formation of lithium nitride supplementary lithium agent. The lithium nitride supplementary lithium agent has high stability, which is conducive to the release of lithium ions at a suitable rate during the cycle and improves the structural stability of composite lithium iron phosphate.
[0175] Furthermore, in some embodiments, the oxygen content in the atmosphere of the second calcination treatment is ≤10ppm, and the humidity of the second calcination treatment is ≤0.1%; after the second calcination treatment is completed, the material is cooled to ≤100℃ and then screened and iron removed to obtain composite lithium iron phosphate.
[0176] In the technical solution of this application embodiment, the above treatment helps to improve the purity of the composite lithium iron phosphate, reduce the probability of side reactions, and improve the cycle stability of the composite lithium iron phosphate.
[0177] Thirdly, embodiments of this application provide a positive electrode sheet, including a current collector and a positive electrode active material, a conductive agent, and a binder located on one or both sides of the current collector; the positive electrode active material is the composite lithium iron phosphate in the embodiments of the first aspect of this application, or the composite lithium iron phosphate prepared by the preparation method in the embodiments of the second aspect of this application, which has good electrochemical performance.
[0178] Fourthly, embodiments of this application provide a secondary battery, including a positive electrode, a negative electrode, and a separator according to the second aspect of this application, which has high energy density and coulombic efficiency.
[0179] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0180] I. Preparation Method
[0181] Example 1
[0182] One embodiment of the composite lithium iron phosphate of this application is described below, and the preparation method of the composite lithium iron phosphate in this embodiment is as follows:
[0183] S1, lithium carbonate, phosphoric acid, ferrous oxalate and glucose are mixed so that the molar ratio of lithium, phosphorus and iron is 0.93:1:1; then air jet milling is performed until the D50 particle size of the solid particles is 5.5 μm to obtain the first mixture;
[0184] S2, add pure water at a mass of 0.22 times that of the first mixture to the first mixture, and perform slurry treatment to obtain slurry material;
[0185] S3, put the slurry into the furnace, introduce nitrogen, control the oxygen content ≤10ppm and the humidity ≤5%, and carry out the first calcination treatment. The heating rate of the first calcination treatment is 100℃ / h, the temperature is 700℃, and the time is 6h. The material obtained from the first calcination treatment is subjected to air jet milling to obtain the first calcined product with a D50 particle size of 1.8μm.
[0186] S4, mix asphalt (ZR type petroleum asphalt from Hebei Zhengri Energy Technology Development Co., Ltd.) and lithium powder (average particle size of 1.5μm), heat under vacuum until the asphalt softens, then mix for 30 minutes using a double cone mixer, and then cool with cooling water until the asphalt solidifies to obtain the second mixture; wherein, the mass ratio of asphalt to lithium powder is 1:8.
[0187] S5, the second mixture and the first calcined product are mixed to obtain the third mixture;
[0188] S6. The third mixture is placed in a rotary kiln, nitrogen is introduced, and the volume fraction of oxygen in the rotary kiln is controlled to be below 10 ppm, the volume fraction of nitrogen to be above 99.9%, and the humidity to be ≤0.1%. The heating rate is 100℃ / h, and the temperature is raised to 500℃ for a second calcination treatment, held for 2 hours, and then cooled to a material temperature ≤100℃. After sieving and iron removal, the composite lithium iron phosphate is obtained; wherein the core includes lithium-deficient phase lithium iron phosphate particles with the chemical formula Li. 0.93 FePO4, with a shell consisting of carbon materials and Li3N, the chemical formula of the composite lithium iron phosphate is Li 0.93 FePO4 / C·0.04Li3N / C.
[0189] Example 2
[0190] One embodiment of the composite lithium iron phosphate of this application is described below, and the preparation method of the composite lithium iron phosphate in this embodiment is as follows:
[0191] S1, Lithium carbonate, phosphoric acid, ferrous oxalate, and glucose are mixed to a molar ratio of lithium, phosphorus, and iron of 0.93:1:1; then air jet milling is performed until the D50 particle size of the solid particles is 3 μm to obtain the first mixture;
[0192] S2, add pure water with a mass of 0.1 times that of the first mixture to the first mixture, and perform slurry treatment to obtain slurry material;
[0193] S3, put the slurry into the furnace, introduce nitrogen, control the oxygen content ≤10ppm and the humidity ≤5%, and carry out the first calcination treatment. The heating rate of the first calcination treatment is 50℃ / h, the temperature is 600℃, and the time is 8h. The material obtained from the first calcination treatment is subjected to air jet milling to obtain the first calcined product with a D50 particle size of 1μm.
[0194] S4, mix asphalt (ZR type petroleum asphalt from Hebei Zhengri Energy Technology Development Co., Ltd.) and lithium powder (average particle size of 1μm), heat under vacuum until the asphalt softens, then mix for 30 minutes using a double cone mixer, and then cool with cooling water until the asphalt solidifies to obtain the second mixture; wherein, the mass ratio of asphalt to lithium powder is 1:8.
[0195] S5, the second mixture and the first calcined product are mixed to obtain the third mixture;
[0196] S6. The third mixture is placed in a rotary kiln, nitrogen is introduced, and the volume fraction of oxygen in the rotary kiln is controlled to be below 10 ppm, the volume fraction of nitrogen to be above 99.9%, and the humidity to be ≤0.1%. The heating rate is 50℃ / h, and the temperature is raised to 400℃ for a second calcination treatment, held for 3 hours, and then cooled to a material temperature ≤100℃. After sieving and iron removal, the composite lithium iron phosphate is obtained; wherein the core includes lithium-deficient phase lithium iron phosphate particles with the chemical formula Li. 0.93 FePO4, with a shell consisting of carbon materials and Li3N, the chemical formula of the composite lithium iron phosphate is Li 0.93 FePO4 / C·0.04Li3N / C.
[0197] Example 3
[0198] One embodiment of the composite lithium iron phosphate of this application is described below, and the preparation method of the composite lithium iron phosphate in this embodiment is as follows:
[0199] S1, Lithium carbonate, phosphoric acid, ferrous oxalate, and glucose are mixed to a molar ratio of lithium, phosphorus, and iron of 0.93:1:1; then air jet milling is performed until the D50 particle size of the solid particles is 8 μm to obtain the first mixture;
[0200] S2, add 0.3 times the mass of pure water to the first mixture and perform slurry treatment to obtain slurry material;
[0201] S3, put the slurry into the furnace, introduce nitrogen, control the oxygen content ≤10ppm and the humidity ≤5%, and carry out the first calcination treatment. The heating rate of the first calcination treatment is 150℃ / h, the temperature is 800℃, and the time is 4h. The material obtained from the first calcination treatment is subjected to air jet milling to obtain the first calcined product with a D50 particle size of 3μm.
[0202] S4, mix asphalt (ZR type petroleum asphalt from Hebei Zhengri Energy Technology Development Co., Ltd.) and lithium powder (average particle size of 3μm), heat under vacuum until the asphalt softens, then mix for 30 minutes using a double cone mixer, and then cool with cooling water until the asphalt solidifies to obtain the second mixture; wherein, the mass ratio of asphalt to lithium powder is 1:8.
[0203] S5, the second mixture and the first calcined product are mixed to obtain the third mixture;
[0204] S6. The third mixture is placed in a rotary kiln, nitrogen is introduced, and the volume fraction of oxygen in the rotary kiln is controlled to be below 10 ppm, the volume fraction of nitrogen to be above 99.9%, and the humidity to be ≤0.1%. The heating rate is 150℃ / h, and the temperature is raised to 600℃ for a second calcination treatment, held for 1 hour, and then cooled to a material temperature ≤100℃. After sieving and iron removal, the composite lithium iron phosphate is obtained; wherein the core includes lithium-deficient phase lithium iron phosphate particles with the chemical formula Li. 0.93 FePO4, with a shell consisting of carbon materials and Li3N, the chemical formula of the composite lithium iron phosphate is Li 0.93 FePO4 / C·0.04Li3N / C.
[0205] Example 4
[0206] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that the molar ratio of lithium, phosphorus and iron in S1 is 0.95:1:1.
[0207] Example 5
[0208] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that the molar ratio of lithium, phosphorus and iron in S1 is 0.9:1:1.
[0209] Example 6
[0210] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that the molar ratio of lithium, phosphorus and iron in S1 is 0.85:1:1.
[0211] Example 7
[0212] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that the molar ratio of lithium, phosphorus and iron in S1 is 0.98:1:1.
[0213] Example 8
[0214] One embodiment of the composite lithium iron phosphate described in this application differs from that in Example 1 in that the amounts of the second mixture and the first calcined product added to the third mixture are adjusted so that the chemical formula of the final composite lithium iron phosphate is Li. 0.93 FePO4 / C·0.03Li3N / C.
[0215] Example 9
[0216] One embodiment of the composite lithium iron phosphate described in this application differs from that in Example 1 in that the amounts of the second mixture and the first calcined product added to the third mixture are adjusted so that the chemical formula of the final composite lithium iron phosphate is Li. 0.93 FePO4 / C·0.05Li3N / C.
[0217] Example 10
[0218] One embodiment of the composite lithium iron phosphate described in this application differs from that in Example 1 in that the amounts of the second mixture and the first calcined product added to the third mixture are adjusted so that the chemical formula of the final composite lithium iron phosphate is Li. 0.93 FePO4 / C·0.017Li3N / C.
[0219] Example 11
[0220] One embodiment of the composite lithium iron phosphate described in this application differs from that in Example 1 in that the amounts of the second mixture and the first calcined product added to the third mixture are adjusted so that the chemical formula of the final composite lithium iron phosphate is Li. 0.93 FePO4 / C·0.067Li3N / C.
[0221] Example 12
[0222] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that, in S4, lithium powder is replaced with an equal molar amount of lithium carbonate (average particle size of 1.5 μm).
[0223] Example 13
[0224] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that the mass ratio of asphalt to lithium powder (average particle size of 1.5 μm) is 1:5.
[0225] Example 14
[0226] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that the mass ratio of asphalt to lithium powder (average particle size of 1.5 μm) is 1:10.
[0227] Example 15
[0228] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that the mass ratio of asphalt to lithium powder (average particle size of 1.5 μm) is 1:3.
[0229] Example 16
[0230] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that the mass ratio of asphalt to lithium powder (average particle size of 1.5 μm) is 1:12.
[0231] Example 17
[0232] One embodiment of the composite lithium iron phosphate of this application differs from that of Embodiment 1 in that, in S3, the temperature of the first calcination treatment is 900°C and the time is 8 hours.
[0233] Example 18
[0234] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that, in S3, the temperature of the first calcination treatment is 500°C and the time is 2 hours.
[0235] Example 19
[0236] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that, in S6, the temperature of the second calcination treatment is 700°C and the time is 4 hours.
[0237] Example 20
[0238] One embodiment of the composite lithium iron phosphate of this application differs from that of Example 1 in that, in S6, the temperature of the second calcination treatment is 350°C and the time is 0.5h.
[0239] Comparative Example 1
[0240] A composite lithium iron phosphate, the preparation method of which differs from that of Example 1, is that in S1, the molar ratio of lithium, phosphorus and iron is 1:1:1; and in S4, no lithium powder is added.
[0241] Comparative Example 2
[0242] A composite lithium iron phosphate, the preparation method of which differs from that of Example 1, is that no lithium powder is added in S4.
[0243] II. Testing Methods
[0244] 1. Property testing of the first calcined product
[0245] Mass fraction of carbon: tested using an infrared carbon-sulfur analyzer.
[0246] 2. Property testing of composite lithium iron phosphate
[0247] (1) Mass fraction of carbon: tested using an infrared carbon-sulfur analyzer;
[0248] (2) Mass fraction of nitrogen: determined by the Kjeldahl method;
[0249] (3) Mass fraction of lithium: tested by ICP-OES; content of free lithium ions: determined by potentiometric titration.
[0250] (4) Mass fraction of iron: tested using ICP-OES;
[0251] (5) Mass fraction of phosphorus: tested using ICP-OES;
[0252] (6) BET specific surface area: tested using a TriStarⅡ3030plus specific surface area analyzer from Micromeritics, USA;
[0253] (7) Compacted density: Compacted under 3.0T pressure for 30s, and tested using a compaction density meter;
[0254] (8) Tap density: A certain amount of composite lithium iron phosphate powder was placed in a glass graduated cylinder with a volume of 25 cm³. 3 The scale height is 135mm. The vibration is performed 1000 times under the conditions of 3mm amplitude and 100 times / min to obtain the tap density.
[0255] (9) Powder resistivity: Tested using a powder resistivity tester under a pressure of 10 MPa;
[0256] (10) pH value: Take 10g of composite lithium iron phosphate powder and 90g of ethanol, mix them to obtain a mixture, let it stand for 10min, and then use a pH meter to test the pH value of the solution, which is the pH value of composite lithium iron phosphate.
[0257] (11) Magnetic material content: The content shall be determined according to the method specified in HG / T 4701-2021;
[0258] (12) Particle size distribution: D50, D90 and D10 particle sizes were measured using a Malvern laser particle size analyzer, with ethanol as the dispersion solvent;
[0259] (13) Average thickness of carbon material: The thickness data of the shell of 10 composite lithium iron phosphate particles after the lithium replenishment agent was removed were observed and recorded by transmission electron microscopy. Three points were taken for each particle and the average value was taken.
[0260] (14) Average particle size of lithium iron phosphate particles in lithium-deficient phase: The particle size of lithium iron phosphate particles in lithium-deficient phase of 10 composite lithium iron phosphate particles was observed and recorded by transmission electron microscopy. Three points were taken for each particle for testing, and the average value of the results was taken.
[0261] (15) Average particle size of lithium supplementer particles: The particle size of lithium supplementer particles in 10 composite lithium iron phosphate particles was observed and recorded by transmission electron microscopy. Three points were taken for each particle for testing, and the average value was taken.
[0262] (16) Morphology: Tested using a scanning electron microscope.
[0263] 3. Properties test of secondary batteries
[0264] 1) Preparation of the positive electrode sheet:
[0265] The components of composite lithium iron phosphate, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 90:5:5. N-methylpyrrolidone (NMP) was weighed in a slurry with a total mass fraction of 50% for composite lithium iron phosphate, graphite, and PVDF. The above components were then mixed to form a slurry. The slurry was then coated onto aluminum foil to a thickness of 200 μm and subsequently vacuum dried to obtain the positive electrode sheet.
[0266] 2) Battery assembly:
[0267] A coin cell battery was assembled using a lithium metal sheet as the counter electrode, Celgard 2400 as the separator, and a solution of lithium hexafluorophosphate (1 mol / L) and EC, DMC, and EMC in a 1:1:1 volume ratio as the electrolyte. The battery was tested at room temperature, with initial charge / discharge capacity at 0.2C and 1C, and capacity retention after 1000 cycles at 1C. The charge / discharge voltage was limited to 2.00V~3.75V.
[0268] III. Analysis of Test Results for Each Embodiment and Comparative Example
[0269] The performance test results of the examples and comparative examples are shown in Tables 1-3.
[0270] Table 1-1
[0271]
[0272] Table 1-2
[0273]
[0274] Table 2
[0275]
[0276] Table 3
[0277]
[0278] The test results above show that the composite lithium iron phosphate in this embodiment has good discharge capacity, and when applied to secondary batteries, it exhibits high initial coulombic efficiency, as well as good rate performance and cycle performance. Comparing the test results of Example 1, Comparative Example 1, and Comparative Example 2, it can be seen that when the core is LiFePO4 and the shell does not contain a lithium replenishing agent, the 1C discharge specific capacity of the composite lithium iron phosphate decreases significantly, and the cycle performance also deteriorates significantly. Furthermore, when the shell does not contain a lithium replenishing agent, the lithium-deficient lithium iron phosphate particles in the core further reduce the 1C discharge specific capacity and cycle stability of the composite lithium iron phosphate.
[0279] Comparing the performance test results of Examples 4-7, it can be seen that when the core-deficient lithium iron phosphate has the chemical formula Li... x When FePO4 is used and x is 0.90~0.95, the composite lithium iron phosphate exhibits significantly higher charging capacity, discharging capacity, rate performance, and cycle performance.
[0280] Comparing the performance test results of Examples 8-11, it can be seen that when the molar ratio of lithium iron phosphate in the lithium iron phosphate composite to the lithium replenishing agent is 1:(0.03~0.05), its rate performance and cycle performance are significantly better when applied to secondary batteries.
[0281] Comparing the performance test results of Example 1 and Example 12, it can be seen that when the lithium supplement is Li3N, the overall electrochemical performance of the composite lithium iron phosphate is better.
[0282] Comparing the performance test results of Examples 13-16, it can be seen that when the mass ratio of lithium powder (second lithium source) to asphalt (second carbon source) is (5-10):1, the capacity of the composite lithium iron phosphate is significantly higher.
[0283] Figure 3 The image shows an SEM image of the composite lithium iron phosphate in Example 1. As can be seen from the image, the composite lithium iron phosphate in this example has good primary particle uniformity, which helps to improve the overall performance of the secondary battery.
[0284] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A composite lithium iron phosphate, characterized in that, It includes a core and a shell, the shell covering at least a portion of the surface of the core; The core comprises lithium iron phosphate particles in a lithium-deficient phase, and the shell comprises carbon material and lithium replenishing agent particles, wherein the carbon material coats at least a portion of the surface of the lithium replenishing agent particles.
2. The composite lithium iron phosphate according to claim 1, characterized in that, Includes at least one of the following features: (1) The average particle size of the lithium iron phosphate particles in the lithium-deficient phase is 0.20 μm to 0.45 μm; (2) In the shell layer, the average particle size of the lithium replenishing agent particles is 0.04 μm to 0.15 μm; (3) The average thickness of the carbon material is 2 nm to 10 nm; (4) The carbon material is at least one of graphite, graphene, carbon nanotubes, carbon nanofibers, and amorphous carbon; (5) The mass fraction of carbon in the composite lithium iron phosphate is 1.3% to 3.3%.
3. The composite lithium iron phosphate according to claim 1, characterized in that, Includes at least one of the following features: (1) The chemical formula of the lithium iron phosphate in the lithium-deficient phase is Li x FePO4, where x is 0.85~0.98; (2) The molar ratio of the lithium iron phosphate in the lithium-deficient phase to the lithium replenishing agent is 1:(0.015~0.07). (3) In the Raman spectrum of the composite lithium iron phosphate, the peak intensity of peak D is I. D The peak intensity of peak G is I G I D / I G The value is 0.65~0.
8.
4. The composite lithium iron phosphate according to any one of claims 1 to 3, characterized in that, Includes at least one of the following features: (1) The specific surface area of the composite lithium iron phosphate is 9.0 m². 2 / g ~15.0m 2 / g; (2) The compaction density of the composite lithium iron phosphate is 2.1 g / mL ~ 2.6 g / mL; (3) The tap density of the composite lithium iron phosphate is 0.85 g / mL to 1.50 g / mL; (4) The lithium replenishing agent is Li3N.
5. A method for preparing composite lithium iron phosphate, characterized in that, Includes the following steps: The first lithium source, phosphorus source, iron source, and first carbon source undergo a first mixing process to obtain a first mixture; The first mixture is then subjected to pulping treatment to obtain a pulped material; The slurry is subjected to a first calcination treatment under a protective atmosphere to obtain a first calcined product; The second lithium source and the second carbon source are subjected to a second mixing process to obtain a second mixture; The first calcined product is mixed with the second mixture to obtain a third mixture; The third mixture is subjected to a second calcination treatment under nitrogen or an inert atmosphere to obtain the composite lithium iron phosphate. The composite lithium iron phosphate comprises a core and a shell, the shell covering at least a portion of the surface of the core, the core comprising lithium iron phosphate in a lithium-deficient phase, and the shell comprising carbon material and a lithium replenishing agent, the carbon material covering at least a portion of the surface of the lithium replenishing agent.
6. The method for preparing composite lithium iron phosphate according to claim 5, characterized in that, Includes at least one of the following features: (1) The temperature of the first calcination treatment is 500℃~900℃, and the time of the first calcination treatment is 2h~8h; (2) The temperature of the second calcination treatment is 350℃~700℃, and the time of the second calcination treatment is 0.5h~4h.
7. The method for preparing composite lithium iron phosphate according to claim 5 or 6, characterized in that, Includes at least one of the following features: (1) The first mixture is obtained by first mixing treatment of the first lithium source, phosphorus source, iron source and first carbon source. The first mixture is obtained by mixing the first lithium source, the phosphorus source, the iron source and the first carbon source and then pulverizing them until the D50 particle size of the solid particles is 3μm~8μm. (2) In the first mixture, the molar ratio of lithium, phosphorus and iron is (0.85~0.98):1:1; (3) The first lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, and lithium phosphate; (4) The phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, iron phosphate, and diammonium hydrogen phosphate; (5) The iron source includes at least one of ferrous oxalate, ferrous phosphate, ferrous sulfate, and ferrous chloride; (6) The first carbon source includes at least one of glucose, starch, polyvinyl alcohol, citric acid, urea, graphite, graphene, and carbon nanotubes; (7) The mass fraction of carbon in the first calcined product is 2.2%~2.4%; (8) The mass ratio of the second lithium source to the second carbon source is (5~10):1; (9) The second lithium source includes at least one of lithium powder and lithium nitride; (10) The second carbon source includes at least one of bitumen and paraffin; (11) The second lithium source is lithium powder and the second carbon source is asphalt. The second lithium source and the second carbon source are mixed and heated until the asphalt softens. After mixing, the mixture is cooled until the asphalt solidifies to obtain the second mixture.
8. The method for preparing composite lithium iron phosphate according to claim 7, characterized in that, The second lithium source is lithium powder, and the second carbon source is pitch. The third mixture is subjected to a second calcination treatment under a nitrogen atmosphere.
9. A positive electrode sheet, characterized in that, It includes a current collector and a positive electrode active material, a conductive agent, and a binder located on one or both sides of the current collector; the positive electrode active material includes the composite lithium iron phosphate according to any one of claims 1 to 4, or the composite lithium iron phosphate prepared by the method of preparing the composite lithium iron phosphate according to any one of claims 5 to 8.
10. A secondary battery, characterized in that, It includes a positive electrode, a negative electrode, and a separator, wherein the positive electrode is the positive electrode as described in claim 9.
Citation Information
Patent Citations
Lithium nitride composite material and preparation and application
CN111224077A
Lithium iron phosphate composite material containing lithium supplement agent, preparation method and application of lithium iron phosphate composite material and battery containing lithium iron phosphate composite material
CN115353085A
Preparation method of lithium iron phosphate composite positive electrode material capable of self-supplementing lithium
CN116435501A
Environment-friendly repairing and regenerating process for lithium iron phosphate
CN117673537A
Lithium supplement agent, lithium iron phosphate battery repair material and preparation method of lithium iron phosphate battery repair material
CN117776273A